THE IMPACT OF STRATEGIC THINKING AND MARKETING CREATIVITY IN MARKETING DECISIONS - Ali, Maison Khaleefah (International Journal of Psychosocial Rehabilitation, 2020)
The general objectives of the reality study from any service organization requires consideration of the senior management of that organization because it is capable of strategic thinking that guides the organization towards creativity and therefore the ability to think strategically in various activities that take into account the exploitation of all available resources in a way that benefits the organization. Strategic thinking is one of the most important ways to take the necessary measures and procedures to create a solid mechanism t o provide basic information for marketing decision-makers, as marketing decisions is what most organizations seek to achieve to ensure the completion of their plans Decision-making is an important priority for any organization that seeks to achieve its objectives. Because of the importance of this topic for business organizations, the researcher went to study (strategic thinking) as an independent variable and (marketing decisions) as a dependent variable because the latter is what all organizations strive to ensure the optimum achievement of all future plans. Based on the above, this study will be divided into four sections, the first chapter under the title of research methodology and previous studies divided into two parts, the first deals with the method ology and method and the hypothesis scheme, while the second part deals with some previous studies. The second chapter deals with the theoretical aspect of the research in which the researcher lists the most important concepts of strategic thinking and marketing decisions divided into two parts, the first part deals with strategic thinking, while the second part deals with marketing decisions. The third chapter is a practical aspect of the research divided into two parts, the first deals with the definition of the research sample, the second is concerned with analyzing the answers of the research sample, and finally the fourth section of the conclusions and recommendations